Underworld. Rise of the Lycans [videorecording (Blu-Ray)] - Tatopoulos, Patrick; Sheen, Michael; Nighy, Bill, 1949-; Mitra, Rhona, 1976- (Sony Pictures Home Entertainment, 2009)
A Lycan rallies his fellow werewolf slaves together in a rebellion against the vampire Death Dealers, beginning a centuries-long feud between the two races.